A sport for all programme in school: girls' experiences. Issue 3 (4th March 2019) - Carlman, Peter; Hjalmarsson, Maria
Abstract: This article examines a Swedish Sport for All Programme (SAP) in school. We use a case study to discuss girls' debut in alternative sports programme organized in collaboration between school and the sports movement. The empirical data are derived from repeated focus group interviews with one group of seven 10-year-old girls participating in one SAP. The analyses focus on their subjective experiences and how broader gender structures influence these experiences. Drawing on the results of this study, we argue that certain sports can be interpreted as oppressive activities that produce asymmetric power relationships between different groups of children. Simultaneously, the girls see the idea of sports as joyful activities, without male abuse and oppression or hierarchical gender relationships. Based on the girls' accounts, we claim that both the leaders and the children actively reproduce gender stereotypes in the SAP.